Iranian nurses’ perception of spirituality and spiritual care: a qualitative content analysis study - Mahmoodishan, Gholamreza (Tehran University of Medical Sciences, 2010)
The purpose of the present study was to explore nurses’ perception about spirituality and spiritual care. A qualitative content analysis approach was conducted on 20 registered nurses interviewed using unstructured strategy in 2009. Three themes emerged from the data analysis: 1) “meaning and purpose of work and life” including ‘spiritualistic view to profession’, ‘commitment and professional responsibility’, and ‘positive attitude’; 2) “religious attitude” including ‘God approval’, ‘spiritual reward’, ‘taking advice’, ‘inner belief in the Supreme Being’, ‘faith-based interactions and altruism’; 3) “transcendence-seeking” including ‘need for respect’ and ‘personal–professional transcendence’. Therefore, the spirituality produces maintenance, harmony and balance in nurses in relation to God. Spiritual care focuses on respecting patients, friendly and sympathetic interactions, sharing in rituals and strengthening patients and nurses’ inner energy. This type of spirituality gives a positive perspective to life and profession, peaceful interactions, a harmonious state of mind, and acts as a motivator among nurses to promote nursing care and spirituality.